Focus of Experience in 21st Century Philippine Literature: A Content Analysis - CASIL-BATANG, PAULINE GRACE (International Journal of Arts, Sciences and Education, 2021)
This study generally aimed to examine representations of males and females in the 21st century Philippine literature found in narratives specifically in the short stories taken from each of the timeframes of 21st century, 2001-2006; 2007-2012; and 2013-present. Specifically, it looked into how females and males are represented in terms of focus of experience. The study made use of mixed-method, qualitative and quantitative research design, and used narratives in the form of short stories taken from 21st Century Philippine literature to be the corpus of analysis. The narratives are all winners of first (1st) prize Palanca award and represent the three timeframes of the 21st century, 2001-2006; 2007-2012; and 2013 to present. The data from the three narratives were content analyzed with the use of quantification and qualification of statements. Based on the results of the study, women across all timeframes still struggle for their position in the society. Their battle against gender inequality continues even until this time. The three narratives reflect these findings.